Dimensions of anxiety sensitivity as a mediator between trait anxiety and depression - Lauri Korajlija, Anita (Array, 2013)
Objectives: A great number of research suggests that anxiety sensitivity (AS) may operate as a vulnerability factor, not only for anxiety disorders, but for psychopathology more broadly, and most notably, depression and depressive symptoms. The vast majority of the AS-depression literature has centered on relation between AS and its dimensions and levels of depression, while considerably less attention has been paid to this relation with regard to trait anxiety and specific symptoms of depression. The aim of this study was to examine possible mediating role of AS, more specifically its dimensions, in relationship between trait anxiety and specific symptoms of depression. Methods: The study was conducted on the normative nonclinical sample of adults (N=1541) using State-trait Anxiety Inventory, BDI–II and Anxiety Sensitivity Index. Results: The results of hierarchical linear multiple regressions showed that among AS dimensions, only cognitive concerns signiﬁcantly predict depression symptoms even after controlling for trait anxiety. Cognitive concerns have mediating role in relationship between trait anxiety and cognitive, affective and somatic symptoms of depression. Conclusions: These ﬁndings are in line with previous theorizing that the AS-depression relation cannot be solely explained by the co-occurrence of anxiety and depression symptoms. The ﬁndings will be discussed in the context of the speciﬁcity of AS as a risk factor and potential practical implications will be proposed.